CYTOTOXICITY ASSAY OF ACTIVE COMPOUNDS OF Gynura procumbens (Lour) Merr TO SEVERAL CELL LINE - Rina Handayani; Sugiyanto .; Nina Salamah (Indonesian Journal of Pharmacy, 2001)
The leaves of Dewa (Gynura procumbens (Lour) Merr), is utilized in traditional medicine as anticancer, had been reported to contain flavonoid derivatives and supposed to have cytotoxic properties. Hence, these particular substances might be useful to be developed as anticancer in the future. Research on ethanol extract of Gynura procumbens (Lour) Merr leaves as anticarcinogen has been carried out, using toxicity assay model to vero, myeloma and lymphocyte cells. This research applied varied concentrations and adriamycin as a positive control. Observation to the cell growth inhibition was carried out for 4 days. The result showed that the dominant substance (the third spot of paper chromatogram) inhibit the growth of vero and myelome cells but lymphocyte cell. The LC50 of this substance to myelome, vero and lymphocyte cells were < 82.8 g/ml, 103.86 g /ml and > 2650 g/ml, respectively, whereas the LC50 of adriamycin to the cell lines were < 0.015 g /ml. Therefore, substances obtained from Gynura procumbens (Lour) Merr leaves might be developed against cancer.Key word: Gynura procumbens (Lour) Merr, mieloma